ANKLE-BRACHIAL INDEX BEHAVIOR AFTER SUBMAXIMAL EXERCISE IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE (Fiep Bulletin - online, 2016)
Chronic obstructive (COPD) Pulmonary Disease presents inflammatory profile and may result in progressive peripheral arterial disease (PAD), as the Ankle-Brachial Index (ABI) allows the measurement of blood flow in the lower limbs (MI). Objective is to evaluate the ABI before (ABIpre) and after (ABIpost) vertical cycle ergometer exercise in COPD patients participating in the Pulmonary Rehabilitation Program with PAD. The ABI was accessed by measuring systolic blood pressure (SBP) of the ankle and brachial SBP bilaterally through sphygmomanometer and Doppler Vascular Laptop. Measurements taken before and after submaximal for 30-40 minutes through vertical cycle ergometer for MI with 60% of FC determined by the Karvonen method modified for FC reserve aerobic exercise. Evaluated 06 patients with a median age of 64 (58-70) years and BMI 22 (20-27) kg/m2. Showed a significant difference between the ABIpre and ABIpost vertical cycle ergometer exercise in patients evaluated (ABIpre: 0.84; ABIpost 0.94; p = 0.007). The results indicate that COPD patients with PAD showed acute improvement of peripheral arterial vascularization after exercise, this finding being translated by an increase Ankle Brachial Index.
Keywords: COPD; peripheral artery disease; rehabilitation.